2016
DOI: 10.1038/srep35928
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the diversity of extracellular vesicles using high-dimensional flow cytometry analyses

Abstract: Extracellular vesicles (EV) are small membrane vesicles produced by cells upon activation and apoptosis. EVs are heterogeneous according to their origin, mode of release, membrane composition, organelle and biochemical content, and other factors. Whereas it is apparent that EVs are implicated in intercellular communication, they can also be used as biomarkers. Continuous improvements in pre-analytical parameters and flow cytometry permit more efficient assessment of EVs; however, methods to more objectively di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 54 publications
(139 reference statements)
0
76
0
Order By: Relevance
“…As the size of the particles is smaller than the diameter of the lasers used in the flow cytometer, there are the same considerations of co‐incidence as with isolated organelles. As well as in conventional flow cytometry, exosomes and microvesicles can also be studied using other cytometric technologies such as imaging flow cytometry . See Chapter V Section 2.7 Extracellular vesicles for more detailed information.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…As the size of the particles is smaller than the diameter of the lasers used in the flow cytometer, there are the same considerations of co‐incidence as with isolated organelles. As well as in conventional flow cytometry, exosomes and microvesicles can also be studied using other cytometric technologies such as imaging flow cytometry . See Chapter V Section 2.7 Extracellular vesicles for more detailed information.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…To examine EV heterogeneity at a population level, the Boilard lab took advantage of FACS followed by spanning‐tree progression analysis of density‐normalized events (SPADE) analysis, which clusters events based on similarity and allows for better identification of rare subpopulations. EVs isolated from stimulated platelets and erythrocytes were organized based on the expression of CD41a, CD235a, phosphatidylserine, mitochondrial content, size, and complexity (granularity).…”
Section: Emerging Approaches To Study Ev Heterogeneitymentioning
confidence: 99%
“…The combination of flow cytometry and spanning‐tree progression analysis of density‐normalized events (SPADE) as computational approach permits a better appreciation of the heterogeneity of microparticles ( i.e . cellular source, compartment origin, organelle content and surface markers expression) . Using flow cytometry and SPADE to assess presence of naked organelles and mitochondria encapsulated in microparticles, it was found that the preparation method had a significant impact on extrusion of mitochondria and that storage duration had no or very modest effect on release .…”
Section: Extracellular Mitochondria As a Biomarkermentioning
confidence: 99%
“…cellular source, compartment origin, organelle content and surface markers expression) . Using flow cytometry and SPADE to assess presence of naked organelles and mitochondria encapsulated in microparticles, it was found that the preparation method had a significant impact on extrusion of mitochondria and that storage duration had no or very modest effect on release . Platelets prepared using the platelet‐rich plasma method contained more extracellular mitochondria than those prepared using apheresis and buffy coat methods, even before storage .…”
Section: Extracellular Mitochondria As a Biomarkermentioning
confidence: 99%